Digital Business Model Innovation: Empirical insights into the drivers and value of Artificial Intelligence - Winter, Johannes (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2021)
The business activities of traditional industrial companies have commonly focused on products and product-related services. Digital pioneers have evolved their offerings into product-service systems that are networked, intelligent, personalized, and adaptable. The speed at which business models must change continues to be underestimated by many market participants, especially when order books are well filled and the pressure to change appears to be low. Industrial and service companies need to adapt to the changes induced by new market players better today than tomorrow to secure future business success and remain competitive in the digital age. The aim of this article is to intensify the debate on digital business model innovation in industry and the service sector and to enrich it with practical examples of the successful implementation of artificial intelligence in products and services.